PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN CITRA PUSKESMAS TERHADAP LOYALITAS PASIEN MELALUI KEPUASAN (STUDI PADA PUSKESMAS WAETUNO KEC. WANGI-WANGI KAB. WAKATOBI) - Muhammad Aswin Mukka Ipo; Murdjani Kamaluddin; Endro Sukotjo; Sudirman Zaid; Nursaban Rommy; Sinarwaty Sinarwaty (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
AbstractThe purpose of this study is to examine and explain the effect of service quality, trust and image on patient loyalty through satisfaction either partially or through mediation at the Waetuno Health Center, Kec. Regency Wangi-Wangi. Wakatobi. This research approach is a survey with an explanatory research design. Data collection was carried out cross-sectionally by using an instrument in the form of a questionnaire. Sampling used the accidental technique so that the number of respondents was 42. The analytical equipment used to test the hypothesis was Partial Least Square (PLS). The results showed that service quality had a positive and significant effect on goals, trust had a positive and significant effect on goals, image had a positive and significant effect on the effect, satisfaction had a positive and significant effect on loyalty, service quality had a positive and significant impact on loyalty, and trust had a significant impact on loyalty. positive and significant effect on loyalty, image has a positive and significant effect on loyalty, service quality has a positive and significant effect on loyalty and trust has a positive and significant effect on loyalty through, and image has a positive and significant effect on loyalty through satisfaction.